Modulation of the hippo-YAP pathway by cyclic stretch in rat type 2 alveolar epithelial cells—a proof-of-concept study - Ran, Xi; Müller, Sabine; Brunssen, Coy; Huhle, Robert; Scharffenberg, Martin; Schnabel, Christian; Koch, Thea; Gama de Abreu, Marcelo; Morawietz, Henning; Ferreira, Jorge M. C.; Wittenstein, Jakob (Frontiers in Physiology, 2023)
Background: Mechanical ventilation (MV) is a life supporting therapy but may also cause lung damage. This phenomenon is known as ventilator-induced lung injury (VILI). A potential pathomechanisms of VILI may be the stretch-induced production and release of cytokines and proinflammatory molecules from the alveolar epithelium. Yes-associated protein (YAP) might be regulated by mechanical forces and involved in the inflammation cascade. However, its role in stretchinduced damage of alveolar cells remains poorly understood. In this study, we explored the role of YAP in the response of alveolar epithelial type II cells (AEC II) to elevated cyclic stretch in vitro. We hypothesize that YAP activates its downstream targets and regulates the interleukin-6 (IL-6) expression in response to 30% cyclic stretch in AEC II. Methods: The rat lung L2 cell line was exposed to 30% cyclic equibiaxial stretch for 1 or 4 hours. Non-stretched conditions served as controls. The cytoskeleton remodeling and cell junction integrity were evaluated by F-actin and Pan-cadherin immunofluorescence, respectively. The gene expression and protein levels of IL-6, YAP, Cysteine-rich angiogenic inducer 61 (Cyr61/CCN1), and connective tissue growth factor (CTGF/CCN2) were studied by real-time polymerase chain reaction (RT-qPCR) and Western blot, respectively. Verteporfin (VP) was used to inhibit YAP activation. The effects of 30% cyclic stretch were assessed by two-way ANOVA. Statistical significance as accepted at p<0.05. Results: Cyclic stretch of 30% induced YAP nuclear accumulation, activated the transcription of YAP downstream targets Cyr61/CCN1 and CTGF/CCN2 and elevated IL-6 expression in AEC II after one hour, compared to static control. VP (2 µM) inhibited YAP activation in response to 30% cyclic stretch and reduced IL-6 protein levels.In rat lung L2 AEC II, 30% cyclic stretch activated YAP, and its downstream targets Cyr61/CCN1 and CTGF/CCN2 and proinflammatory IL-6 expression. Target activation was blocked by a YAP inhibitor. This novel YAP-dependent pathway could be involved in stretch-induced damage of alveolar cells.